A Methodological Approach to Architectural Models as an Integral Part of the Design Process (diségno, 2018)
From ancient times to the present day, architects and engineers have tried to express their designs in materials that allow them totransfer the creations from their mind to the tangible world, bringing them to life through models showing a future or hypotheticalconstructed reality. There have been more than 5,000 years between the first intuitive representations and the current immersivevirtual reality prototypes, over which time the search for a universal graphic representation model has been a constant and three-dimensionalityhas always played an essential role [1].
Keywords: graphic representation; three-dimensionality; models and mockups